2018
DOI: 10.1080/23249935.2018.1547332
|View full text |Cite
|
Sign up to set email alerts
|

Bottleneck mitigation through a variable speed limit system using connected vehicles

Abstract: Variable speed limit (VSL) systems are used to improve the traffic conditions by adjusting the speed limits based on the current traffic situation. Advances in vehicle technology have made it possible to use connected vehicles in VSL systems. Connected vehicles can continuously transmit information about their speed and location, which can be used to estimate the current traffic conditions at arbitrary locations. In this study, we propose a VSL system based on connected vehicles. The aim is to also allow appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Khondaker and Kattan ( 20 ) presented a VSL control algorithm for simultaneously achieving mobility, safety, and environmental benefits in a CV environment. Grumert and Tapani ( 21 ) proposed a VSL system based on CVs to allow for the application of VSLs in connection with non-recurrent bottlenecks. Their results indicated that the VSL system managed to improve traffic efficiency in a majority of the simulated cases ( 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Khondaker and Kattan ( 20 ) presented a VSL control algorithm for simultaneously achieving mobility, safety, and environmental benefits in a CV environment. Grumert and Tapani ( 21 ) proposed a VSL system based on CVs to allow for the application of VSLs in connection with non-recurrent bottlenecks. Their results indicated that the VSL system managed to improve traffic efficiency in a majority of the simulated cases ( 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grumert and Tapani ( 21 ) proposed a VSL system based on CVs to allow for the application of VSLs in connection with non-recurrent bottlenecks. Their results indicated that the VSL system managed to improve traffic efficiency in a majority of the simulated cases ( 21 ). Li et al ( 22 ) propose an MPC strategy of a novel VSL using a line of connected automated vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Real-time traffic information systems, for instance, traveler information messages (TIM), or variable message signs (VMS), are considered as an efficient method to convey messages to drivers with traffic information and upcoming incidents. This method could be embedded in autonomous/CVs (Genders & Razavi, 2016) where CVs provide continuous realtime information sources about their speed and location to estimate the traffic conditions at random locations (Grumert & Tapani, 2020). Sui and Young (2014) developed a linear regression model to identify the impacts of VMS on driver speed behavior under different adverse weather conditions using field data.…”
Section: Based Traveler Information Messagesmentioning
confidence: 99%
“…Perraki et al [20] used the MPC strategy proposed by Roncoli et al [21] to assess CAVs and conventional control measures for a complex real network in a realistic simulation environment. Grumert and Tapani [22] proposed a CV based VSL system in which CVs are used to estimate traffic state and the current speed limit is communicated directly to the CVs.…”
Section: Introductionmentioning
confidence: 99%